Grow out Carp Polyculture by Women : A Case Study from Odisha - H. K. De, D. N. Chattopadhyay, Radheyshyam, G. S. Saha, A. K. Dash, T. S. Satpati, S. Pal, (Indian Journal of Extension Education, 2022)
..